Could it happen here?: moral panic, school shootings, and fear of crime among college students - Schildkraut, Jaclyn (Crime, law and social change, 2015)
Originating in the early 1970s, the concept of moral panic has been used to describe the public’s reaction to a real or perceived threat. Moral panic has been linked to well-known social problems, including muggings, drugs, juvenile ‘delinquency, gangs, and terrorism. More recently, researchers have examined school shootings in this context. Notably absent, however, is a quantitative application of Goode and Ben-Yehuda’s (1994a, 1994b) attributional model of moral panic. The present study examines the five key attributes of moral panic—concern, hostility, consensus, disproportionality, and volatility - as they relate to school shootings and fear of crime among college students. The results indicate that respondents’ fear of crime is the best predictor of students’ subscription to moral panic. Directions for future research, as well as limitations of the present study, also are discussed.